A comparative evaluation of the flow and compaction characteristics of Psidium guajava leaf powder - Majekodunmi , S. O.; Ekundayo , O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The dried leaf of Psidium guajava is wildly used in the treatment of diabetes, gastroenteritis, vomiting, diarrhoea, dysentery, wounds, ulcers, toothache, coughs, sore throat and inflamed gums. The objective of the present research was to study the original flowability and compressibility of Psidium guajava leaf powder and develop its tablet formulations by wet granulation and direct compression. The consolidation behaviors of drug and tablet formulations were studied by using Heckel and Leuenberger equations. Psidium guajava leaf powder showed very poor flowability and compressibility. Kawakita analysis revealed improved flowability for formulations prepared by direct compression and wet granulation techniques. The Heckel plot showed that Psidium guajava leaf powder is soft in nature, poor in die filling and deforms by initial fragmentation. Granules showed higher degree of plasticity and fragmentation than powder and direct compression formulation. The compression parameter for compact formed by direct compression and wet granulation technique indicated that the maximum crushing strength is reached faster at lower pressures of compression. From this study, it is concluded that desired flowability and compressibility of Psidium guajava leaf powder can be obtained by direct compression and wet granulation technique but wet granulation technique is comparatively better.